Antibiotic stewardship in skin infections: a cross-sectional analysis of early-career GP's management of impetigo. Issue 10 (28th October 2019) - Heal, Clare; Gorges, Hilary; van Driel, Mieke L; Tapley, Amanda; Davis, Josh; Davey, Andrew; Holliday, L; Ball, Jean; Najib, Nashwa; Spike, Neil; FitzGerald, Kristen; Magin, Parker
Abstract : Objective: To establish the prevalence and associations of systemic antibiotic prescription for impetigo by early-career general practitioners (GPs) (GP registrars in their first 18 months in general practice). Design: A cross-sectional analysis of data from the Registrar Clinical Encounters in Training (ReCEnT) study. Setting: ReCEnT is an ongoing multisite cohort study of Australian registrars' in-consultation clinical practice across five Australian states. Participants: Registrars participating in ReCEnT from 2010 to 2017. Outcome measures: Management of impetigo with systemic antibiotics. Results: 1741 registrars (response rate 96%) provided data from 384 731 problems identified in 246 434 consultations. Impetigo, on first presentation or follow-up, was managed in 930 (0.38%, 95% CI 0.35 to 0.40) consultations and comprised 0.24% (95% CI 0.23 to 0.26) of problems. 683 patients presented with a new diagnosis of impetigo of which 38/683 (5.6%) were not prescribed antibiotics; 239/683 (35.0%) were prescribed solely topical antibiotics; 306/683 (44.8%) solely systemic antibiotics and 100/683 (14.6%) both systemic and topical antibiotics. The most common systemic antibiotic prescribed was cephalexin (53.5%). Variables independently associated with prescription of systemic antibiotics were an inner regional (compared with major city) location (OR 1.82, 95% CI 1.06 to 3.13; p=0.028), seeking in-consultation information or advice (OR 2.17, 95% CI 1.47 to 3.23; p<0.001) and ordering pathology (OR 2.13, 95% CI 1.37 to 3.33; p=0.01). Conclusions: Australian early-career GPs prescribe systemic antibiotics (the majority broad-spectrum) for a high proportion of initial impetigo presentations. Impetigo guidelines should clearly specify criteria for systemic antibiotic prescription and individual antibiotic choice. The role of non-antibiotic management and topical antiseptics needs to be explored further.